How two pairs of gradient pulses give access to new information about molecular dynamics - Callaghan, Paul T. (Diffusion Fundamentals, 2005)
Pulsed Gradient Nuclear Magnetic Resonance provides direct insight regarding the translational motion of spin-bearing molecules. These methods gain a second dimension when the simple gradient pulse pair is enhanced by a second pair. Where the motion encoding of the two pairs is opposite, flow effects are removed from the echo attenuation, making it possible to measure diffusion in the presence of shear flow, or to measure the stochastic part of dispersive flow, and in particular the velocity auto-correlation function. Where the gradient pulse pairs are stepped in independent dimensions, two-dimensional experiments become possible. One class (Fourier-Fourier) is the Velocity Exchange (VEXSY) experiment in which flow velocities may be correlated at different times. Another class (inverse Laplace-inverse Laplace) is the diffusion correlation (DDCOSY) or diffusion exchange (DEXSY) experiment. This approach has proven of particular value in ascertaining local anisotropies in globally isotropic systems, as well as in the model-free measurement of exchange effects.